Study and application of a novel high-performance grouting material in the management of karst water inrush disasters - Liang, Jingwei; Song, Zilong; Fan, Zezhong; Wang, Xiang (Frontiers in Earth Science, 2025)
Grouting technology is a crucial method for mitigating karst water inrush disasters. However, traditional grouting materials face significant limitations when addressing catastrophic karst water inrush under conditions of high-water pressure, large water inflow, and complex hydraulic environments. To overcome these challenges, this study developed a high-performance modified clay-cement grouting material. A series of indoor experiments were conducted to investigate the effects of the water-to-solid ratio, clay content, and modifier dosage on the material’s grouting performance. The optimal mix ratio was identified as water: cement: clay = 2:1:1, with an admixture dosage of 0.75%, by comparing the engineering performance of the new material against pure cement and traditional cement-clay grouting materials. The applicability and effectiveness of the developed grouting material were further validated in a practical engineering application within a water conservancy hub project in Guiping City, Guangxi Province. Results indicate that the new material not only effectively mitigates the risk of catastrophic karst water inrush but also offers advantages such as low cost, ecological benefits, and environmental sustainability. This study provides reliable technical support for emergency grouting applications and demonstrates potential for wider use.